Muslim Employment in Commonwealth Government Departments and Agencies in the Context of Access and Equity - Umar Bin Amin (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract Government agencies and departments are considered as a collectively owned body and therefore they can be assumed as a reflection of the whole society. But the current research, Muslim Employment in Commonwealth Government Departments and Agencies in the Context of Access and Equity, suggests that migrants face a greater exclusion of Australia from government department in general but Muslim community is bearing the extensive brunt. In this research the exclusion was examined at three different sphere, at national employment level, national government department’s level and managerial levels of government employment. In each sphere it was found that the Muslim community was two times less inclusive thus making it six times excluded from the society overall. After collecting these results and combining them with an academically defined state of inclusion, it yielded new conditions for Harmony as: access and equal opportunities for all Australians while having a sense of being equally valued and have the opportunity of full participation with redistribution of power for the powerless.    Abstrak Instansi pemerintah dan departemen dianggap sebagai badan yang dimiliki secara kolektif dan karena itu mereka dapat diasumsikan sebagai refleksi dari seluruh masyarakat. Tetapi penelitian saat ini, Pekerjaan Muslim di Departemen Pemerintah Persemakmuran dan Instansi dalam Konteks Akses dan Kesetaraan, menunjukkan bahwa migran secara umum menghadapi pengucilan lebih besar dari Australia dari departemen pemerintah di masyarakat tetapi Muslim terpaksa menanggung beban yang luas. Dalam penelitian ini pengucilan diselidiki pada tiga bidang yang berbeda, di tingkat kerja nasional, tingkat departemen pemerintah nasional dan tingkat manajerial kerja pemerintah. Dalam setiap lingkup ditemukan bahwa komunitas Muslim dua kali lebih inklusif sehingga membuatnya enam kali dikucilkan dari masyarakat secara keseluruhan. Setelah mengumpulkan hasil-hasil dan menggabungkannya dengan negara inklusi yang didefinisikan akademis, itu menghasilkan kondisi baru untuk Harmony sebagai: akses dan kesempatan yang sama bagi semua warga Australia sementara memiliki rasa yang sama-sama dihargai dan memiliki kesempatan berpartisipasi penuh dengan redistribusi kekuasaan untuk ketberdayaan. How to Cite : Amin, U. B. (2016). Muslim Employment In Commonwealth Government Departments And Agencies In The Context Of Access And Equity. TARBIYA: Journal Of Education In Muslim Society, 3(1), 1-19. doi:10.15408/tjems.v3i1.3485. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i1.3485